HIYAL SEBAGAI TEORI PEREKAYASA DALAM HUKUM ISLAM - Arifin, Ahmad Fauzan; Erfan, Muhammad; Rizqi, Muhammad; Anshari, Muhammad (MAQASHIDUNA: JURNAL HUKUM KELUARGA ISLAM, 2023)
Abstract:One of the studies in Islami clegal theory is the hiyal theory. In this case, hiyal is an engineering theory (legal fiction) that cancels sharia law and replaces it formally with anotherlaw. In this regard, the discussion in this paper uses asocio-legal method that connects hiyal theory at a conceptual level with case studies of hiyal practices in the fiel dofmarriageand Islamic inheritance. Results of the discussion in this paper: First, the concept of hiyal is still a matter of debate among scholars. There are scholars who allow it with the aimofavoidingharm. However, scholars generally prohibit the use of the hiyal because it can distort Islamic law. Second, hiyal can be categorize dinto three parts:1) Hiyal that is permitted; 2) Hiyal which is prohibited; 3. Hiyal who selaw is still disputed. Third, it relates to a case study of the practice hiyal in the field of marriage regarding the practice of nikah tahlil or nikah muhallil which is acontroversial practice because it involves divorcing the woman's marriage with theaim of making it halal for her ex-husband. This practice is considered by some scholars to be a formof hiyal which is prohibited because it circumvents the original purpose of marriage in Islam. In the field of inheritance, it turns out that hiyal practices are not free. For example, in Gambut  District, Banjar Regency and Amuntai Tengah District, Hulu Sungai Utara Regency, South Kalimantan Province, there are the practice of living in heritance. This division is not known in the division of in heritance in Islam or Westernlaw. The distribution processis carried out by the heir gathering all the heirs and after everyone has gathered, the heir expresses his desireto divide the assets among his heirs. In conditions like this, heirs generally agree to the distribution made by their parents as a formofres pectand devotion to their parents.Keywords: Hiyal, EngineeringTheory, Islamic Law, Marriage, Inheritance.Abstrak:Salah satu kajian dalam teori hukum Islam adalah teori hiyal. Dalam hal ini, hiyal merupakan teori perekayasa (legalfiction) yang membatalkan hukum syara’ dan menggantinya secara formal dengan hukum yang lain. Berkaitan dengan hal tersebut, pembahasan dalam penelitian ini menggunakan metode sosio-legal yang menghubungkan antara teori hiyal dalam tataran konsep dengan studi kasus praktik hiyal di bidang perkawinan dan kewarisan Islam. Hasil pembahasan dalam makalah ini: Pertama, konsep hiyal masih menjadi perdebatan dikalangan ulama. Terdapat kalangan ulama yang membolehkan dengan tujuan menghindari kemudaratan. Namun, umumnya para ulama melarang penggunaan hiyal karena dapat merekayasa hukum Islam. Kedua, hiyal dapat dikategorikan menjadi tiga bagian: 1) Hiyal yang dibolehkan; 2) Hiyal yang dilarang; 3. Hiyal yang masih diperselisihkan hukumnya. Ketiga, berkaitan dengan   studi kasus praktik hiyal bidang perkawinan mengenai praktik nikah tahlil atau nikah muhallil yang menjadi praktik kontroversial karena melibatkan pernikahan pihak wanita untuk diceraikan dengan tujuan menjadikan dia halal bagi mantan suaminya. Praktik ini dianggap oleh sebagian ulama sebagai bentuk hiyal yang dilarang karena mengelak dari maksud asli dari tujuan pernikahan dalam Islam. Adapun dalam bidang kewarisan juga ternyata tidak luput dari praktik hiyal. Sebagai contoh, di Kecamatan Gambut, Kabupaten Banjar dan Kecamatan Amuntai Tengah, Kabupaten Hulu Sungai Utara, Provinsi Kalimantan Selatan terdapat praktik waris hidup. Pembagian ini yang tidak dikenal dalam pembagian waris Islammaupun hukum Barat. Proses pembagian dilakukan dengan cara pewaris mengumpulkan semua ahli waris dan setelah semuanya berkumpul pewaris mengemukakan keinginannya membagi-bagi harta kepada ahli warisnya. Dalam kondisi seperti ini ahli waris umumnya menyetujui pembagian yang dilakukan orang tuanya sebagai wujud penghormatan dan baktinya kepada orang tua.Kata Kunci: Hiyal, Teori Perekayasa, Hukum Islam, Perkawinan, Kewarisan.